Analysis of Strategic Management for Competitive Advantage at Basmalah Store - Diah Kartika Rohman; Misbahul Munir; Ahmadiono (Jurnal Syntax Admiration, 2023)
This research aims to analyze the competitive advantage strategic management applied by Basmalah store. Competitive advantage is key to maintaining and increasing market share in the competitive retail industry. The research method used is a qualitative approach, conducting in-depth interviews with the owner and manager of Basmalah store, as well as direct observation at the store location. The results of the research indicate that Basmalah store has implemented several competitive advantage strategies, including product differentiation, customer service enhancement, and operational efficiency. By maintaining a stock of unique and high-quality products, Basmalah store successfully attracts customers looking for specific items. Additionally, improving customer service through friendly and informative service is also a crucial factor in maintaining customer loyalty. Operational efficiency is also considered crucial in maintaining competitive advantage. Through effective inventory management strategies and the use of technology to monitor store performance, Basmalah can reduce operational costs and improve efficiency. However, this research also identifies some challenges faced by Basmalah store, including price competition from competitors and market demand fluctuations. Therefore, it is recommended that Basmalah store continues to monitor industry trends, innovate in competitive advantage strategies, and maintain a focus on customer satisfaction.